TEMUAN AUDIT: DETERMINAN DAN HUBUNGANNYA TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH DI INDONESIA - Masculine Muhammad Muqorobin (Riset Manajemen dan Akuntansi, 2017)
The objective of this study is to find empirical evidence about the determinants and the relationship with the financial quality reporting of Local Government Financial Report in Indonesia on 2010th budged year. The Factors used in this study areLocal Government revenue, BPK audit opinion on the Financial Government Financial Report, and Local Government assets. This study use480Local Government Finance Reportof 2010¬¬¬th budged year.Multiple regression analysis technique is used in analyzing the data. The results ofthis studyshowevidencethat thenumber ofBPK audit findingssignificantlyaffectedsignificantly andmoderately significantby2of the3variables of the study. These variablesareLocal Government revenue, BPK audit opinion on the Financial Government Financial Report and theothers isdoes notaffecttotalBPKaudit findingsonLocal Government Finance Report of 2010¬¬¬th budged year. Keywords: BPK audit findings, local government financial report, Agency Theory, local government.